Utilizing market waste to create organic waste in Teluk Pandan, Pesawaran - Sugeng P Harianto; Surnayanti Surnayanti; Machya Kartika Tsani; Trio Santoso (Universitas Muhammadiyah Magelang, 2022)
Hanura Village is one of the villages in Teluk Pandan District, Pesawaran Regency. Hanura is an economic center for nearby villages, so the market is quite busy. The market in Hanura Village is very successful because it provides as a central for nearby villages' economies. This is a problem because market waste accumulates and market waste management is not optimal. This program aims to increase public awareness of the need to compost organic waste by training market administrators on how to process waste into organic fertilizer. The method of the program carried out is counseling and training in making compost. According to the pre-test and post-test, there was a 45–60% increase in people's knowledge and how to use compost. The outcomes of this program show that the neighborhood was given the information from the waste management counseling at the compost fertilizer market.